Legal responsibility in the structure of the legal status of foreigners and stateless persons - A. M. Rubanenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to an important and topical issue, that is the essence of legal responsibility as a structural element of the legal status of foreigners and stateless persons. It is noted that the concept of “responsibility” is used by many branches of scientific knowledge, which imbue it with a peculiar meaning determined by their subject. In a broad sense, responsibility is a special relationship between human actions (people, institutions), intentions, as well as evaluations of these actions by other people or society.